GE_GERICHTE P/419/2019 vom 4. Juni 2020 - GE Cour de justice (2020)
IN DUBIO PRO REO;VOL(DROIT PÉNAL);APPROPRIATION ILLÉGITIME;FIXATION DE LA PEINE;REPENTIR SINCÈRE;EXEMPTION DE PEINE | CP.137; CP.139; CPP.350.al1; CP.47; CP.48.letd; CP.53; CPP.436.al2